2018
DOI: 10.21873/anticanres.12594
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Glucan and Coenzyme Q10in Murine Experimental Autoimmune Disease and Cancer

Abstract: There is significant synergy between coenzyme Q and β-glucan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The same anti-inflammatory response was found in graft vs. host disease (Lee et al, 2016). Further, in a model of carrageenan-induced inflammation in the air pouch, CoQ 10 , in combination with the known immunomodulator β-glucan, reduced leukocyte infiltration in lung, nitrite and proinflammatory cytokines IL1α and β levels (Vetvicka and Vetvickova, 2018). In humans, CoQ 10 supplementation significantly lower inflammation markers in individuals with metabolic syndrome (Dludla et al, 2020) or with diabetic nephropathy (Heidari et al, 2018).…”
Section: Age-related Coenzyme Q Depletion and Immune Systemmentioning
confidence: 86%
“…The same anti-inflammatory response was found in graft vs. host disease (Lee et al, 2016). Further, in a model of carrageenan-induced inflammation in the air pouch, CoQ 10 , in combination with the known immunomodulator β-glucan, reduced leukocyte infiltration in lung, nitrite and proinflammatory cytokines IL1α and β levels (Vetvicka and Vetvickova, 2018). In humans, CoQ 10 supplementation significantly lower inflammation markers in individuals with metabolic syndrome (Dludla et al, 2020) or with diabetic nephropathy (Heidari et al, 2018).…”
Section: Age-related Coenzyme Q Depletion and Immune Systemmentioning
confidence: 86%
“…In the last couple of decades, combinational therapy has emerged as a promising strategy for treating several diseases such as cancer [ 5 , 6 ], diabetes [ 7 ], AIDS [ 8 ], hypertension [ 9 ], autoimmune diseases [ 6 ], tuberculosis [ 10 ], infectious diseases [ 11 , 12 ] and even against the recent COVID-19 pandemic [ 13 ]. In context to drug-resistance, ‘drug cocktails’ could be a game-changer as they come with several benefits such as (1) a broadened antimicrobial spectrum, (2) the likelihood of developing drug resistance would reduce substantially as the chances of acquiring resistance towards a novel combination would be much lower, (3) it could be more efficacious against polymicrobial infections, (4) if the exercised drugs act synergistically, i.e., the combined effect of antimicrobial agents used is greater than the sum of their individual effects, it could provide even better pathogen clearance than the single drug alone and that too at a very low concentration, and (5) the lower concentration of antimicrobial agents could minimize the drug toxicity in the host [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CoQ10 may also induce the expression of the transcription factors Nrf2 (nuclear factor erythroid 2-related factor 2), which binds to the antioxidant response element that activates a battery of genes resulting in the expression of antioxidant and detoxifications proteins, in turn resulting in a suppression of the inflammatory response [ 74 ]. A study by Vetvicka et al [ 75 ] indicated the synergistic effect of combined CoQ10 and beta-glucan therapy in the treatment of cancer. Beta-glucan is a glucose polymer with widely described immunomodulatory properties, which in the case of cancer involves activation of immune cells (either directly or via cytokine induction) that are able to directly eradicate the tumour [ 75 ].…”
Section: Coq10 and Immune Function In Cancermentioning
confidence: 99%
“…A study by Vetvicka et al [ 75 ] indicated the synergistic effect of combined CoQ10 and beta-glucan therapy in the treatment of cancer. Beta-glucan is a glucose polymer with widely described immunomodulatory properties, which in the case of cancer involves activation of immune cells (either directly or via cytokine induction) that are able to directly eradicate the tumour [ 75 ]. However, co-treatment of murine breast and lung models with CoQ10 and beta-glucan was found to induce a more pronounced loss of breast tumour volume or number of metastases respectively than either treatment in isolation, although the actual mechanism responsible for therapeutic synergy was not investigated [ 76 ].…”
Section: Coq10 and Immune Function In Cancermentioning
confidence: 99%